Two new species of Leptanilloides Mann, 1823 (Formicidae: Dorylinae) from the Andes of southern Ecuador - Delsinne, Thibaut; Sonet, Gontran; Donoso, David A. (European Journal of Taxonomy, 2015)
Two new species of Leptanilloides are described: L. copalinga Delsinne & Donoso sp. nov., and L. prometea Delsinne & Donoso sp. nov., based on workers collected in the leaf litter and soil of the Andes of southern Ecuador. Both species belong to the L. biconstricta species-group (formally diagnosed here). The metatibial gland, considered a synapomorphy for Dorylinae, is observed in L. prometea sp. nov. but seems absent in L. copalinga sp. nov. We provide a COI DNA barcode for both species and a revised key for the worker caste of all known species in the genus. We also describe a single male identified as a potential new Leptanilloides species on the basis of morphology. Furthermore, its mitochondrial COI gene sequence does not match any previously barcoded species. However, we refrain from giving it a specific name because of our lack of knowledge about the worker caste. So far, half of the 14 Leptanilloides species have been discovered above 1500 m in the mountain forests or páramos of the Ecuadorian Andes, confirming, if needed, the biological significance of these threatened habitats.